3x+x=-(x+2)+1

Simple and best practice solution for 3x+x=-(x+2)+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+x=-(x+2)+1 equation:



3x+x=-(x+2)+1
We move all terms to the left:
3x+x-(-(x+2)+1)=0
We add all the numbers together, and all the variables
4x-(-(x+2)+1)=0
We calculate terms in parentheses: -(-(x+2)+1), so:
-(x+2)+1
We get rid of parentheses
-x-2+1
We add all the numbers together, and all the variables
-1x-1
Back to the equation:
-(-1x-1)
We get rid of parentheses
4x+1x+1=0
We add all the numbers together, and all the variables
5x+1=0
We move all terms containing x to the left, all other terms to the right
5x=-1
x=-1/5
x=-1/5

See similar equations:

| 7n-4=4+11 | | 1.50x=0.50x+25 | | (2x+7)+74x=180 | | 4x+8*7=2800 | | 32x-32x=2 | | 7b=6b+5 | | (-4x+1)(-3x-4)=0 | | 0.04q^2-1.4q+3=0 | | 0.34=0.2x+0.8 | | u-5=-9u+9+3u | | 5/6-11/12y=1/6 | | y-14=19 | | x-6=5-2x | | x/4+x=3/8 | | 1.5+t=0.5 | | (4+5x)+71=180 | | -3D=-4d+7 | | a-8-9=-9a-15-6+12a | | 5-3x=-12 | | 1-7x=13-4x | | -9+n=-5n+9 | | 3(q+(-5)=8) | | 14.7+5x=3.9-4x | | 1/3x-1/5=-2x-4/5 | | 2/3+x=12/9 | | k-97=-82 | | 11y+48=13 | | 13u-9u=36 | | 7x+0.8=56.8 | | -6(1+5n)=-116 | | k-49=23 | | 3a+8=7a+4 |

Equations solver categories